2004
DOI: 10.1086/380102
|View full text |Cite
|
Sign up to set email alerts
|

Potent Cross‐Group Neutralization of Primary Human Immunodeficiency Virus Isolates with Monoclonal Antibodies—Implications for Acquired Immunodeficiency Syndrome Vaccine

Abstract: Human immunodeficiency virus type 1 (HIV-1) is phylogenetically classified into groups and clades (or subtypes). Human neutralizing monoclonal antibodies (nMAbs), originally isolated from individuals infected with HIV-1 group M-clade B, neutralized not only primary HIV-1 clade B isolates in vitro but also primary isolates of other group M clades (A, C, D, E, and F). This corrected the previously held notion that primary HIV-1 isolates are resistant to neutralizing antibodies. Here we show that anti-HIV-1 group… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
32
0

Year Published

2004
2004
2013
2013

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(33 citation statements)
references
References 23 publications
1
32
0
Order By: Relevance
“…HIV-1 neutralizing antibodies have come again to the forefront of research since the recent demonstrations of their protective capacities (Baba et al 2000, Mascola et al 2000, Parren et al 2001, Nishimura et al 2002, Ferrantelli & Ruprecht 2002, Xu et al 2002, Mascola 2002, Xiao et al 2002, Ferrantelli et al 2004). Moreover, their importance in the early control of HIV-1 infection is implied by the finding of immune complexes containing HIV-1 RNA (Dianzani et al 2002), which could be an explanation for the disparity between quantification of viral RNA and of infectious HIV virions (Igarashi et al 1999).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…HIV-1 neutralizing antibodies have come again to the forefront of research since the recent demonstrations of their protective capacities (Baba et al 2000, Mascola et al 2000, Parren et al 2001, Nishimura et al 2002, Ferrantelli & Ruprecht 2002, Xu et al 2002, Mascola 2002, Xiao et al 2002, Ferrantelli et al 2004). Moreover, their importance in the early control of HIV-1 infection is implied by the finding of immune complexes containing HIV-1 RNA (Dianzani et al 2002), which could be an explanation for the disparity between quantification of viral RNA and of infectious HIV virions (Igarashi et al 1999).…”
Section: Discussionmentioning
confidence: 99%
“…Robert-Guroff et al 1985, Weiss et al 1985. In the course of the last three years, however, the high protection obtained in monkeys infused with anti-HIV-1 monoclonal antibodies has increased interest in HIV-1 neutralization (Baba et al 2000, Mascola et al 2000, Nishimura et al 2002, Ferrantelli et al 2004. Studies in animal models have confirmed the importance of HIV-1 neutralizing antibodies (NAb) in HIV-1 infection and efforts to analyze and to induce such antibodies in humans have been increased.…”
mentioning
confidence: 99%
“…122 Another mAb, Clone 3, recognizes a disulfide-dependent conformational epitope located in the immunodominant loop of the ectodomain of gp41 (GCSGKLICTT) and has been shown to neutralize primary isolates. 125,126 It is very interesting to note that mAbs recognizing epitopes 5-7 amino acids upstream to that of Clone 3, are not able to neutralize HIV-1 primary isolates. 59,68 Recently, Ofek and colleagues have determined the crystal structure of the antigen binding fragment of 2F5 in conjunction with 7, 11 and 17-mer peptides of the gp41 membrane proximal region.…”
Section: Epitopes In Variable Regions Of Virus Envelopementioning
confidence: 99%
“…Another infusion of the same mAb cocktail an hour after the virus exposure, followed by another dose on day eight, completely protected animals against infection. 145,148 In a recent study, Ferrantelli and colleagues 126 have demonstrated complete protection of neonatal rhesus macaques against exposure to pathogenic simian-human immunodeficiency virus (SHIV) by human anti-HIV mAbs. In this study, a group of eight animals were orally exposed to the pathogenic SHIV and four of them were given post exposure prophylaxis with three anti-HIV mAbs (2F5, 2G12 and 4E10) at 40 mg/Kg.…”
Section: Protection Against Hiv-1 Infectionmentioning
confidence: 99%
“…Even if the response to this region is very frequent most of the Abs elicited do not present neutralization capacities but instead shown enhancement of infection (Robinson et al, 1990). Only one MAb (clone3) neutralize T-cell laboratory adapted viruses from clade B and three primary isolates from group O (Ferrantelli et al, 2004).…”
Section: Immunodominant Loopmentioning
confidence: 99%